Prevalence, risk factors of forward head posture and its health consequences on physical outcomes among the adult population in Saudi Arabia - M. Hussein, Hisham; Abdelmoniem Ibrahim, Ahmed; Alshubrami , Shatha Saleh; Abdualrahman Alrahili, Remas; Abdullah Alaqil, Munirah; Alshehri, Salihah; Hakami, Ghazi; Alsuwat, Mousa; Abdulrahim Alghamdi, Wajdi; Mohammed Almeshyakhi , Salha; et al. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study investigated the prevalence, risk factors, and health consequences associated with forward head posture (FHP) among Saudi Arabia’s adult population. The authors screened 533 adult males using a photographic technique to calculate the craniovertebral angle (CVA), and used direct questions to determine the average screen time per day, the existence of neck pain, and the average number of pain attacks. Body composition was indicated by body mass index (BMI). The numeric pain rating scale (NPRS) assessed the average neck pain intensity. Of the 533 participants, 211 (39%) demonstrated a CVA of 48° or less, indicating FHP. There was a statistically significant negative correlation between screen time exposure and the value of CVA (r=-.651; p<.001). Similarly, a statistically significant positive correlation existed between BMI and FHP (r= -.470; p<.001). The existence of pain, its intensity, and the average number of attacks were statistically significantly correlated with the CVA (Rpb= -.692; p<.001). (r=-.621; p<.001). (r=-.801; p<.001), respectively. In conclusion, FHP is a common neck problem among adult males in Saudi Arabia. Reducing exposure to smart screens and optimizing body composition could reduce the incidence of FHP and subsequent neck pain.